(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The soil moisture and the soil temperature at 7 a.m. and 1 p.m. were monitored in the lentil field. During the years of studies it was observed that the highest PDI was recorded on March 12 with corresponding soil temperature at 7 a.m. and 1 p.m. and soil moisture were maximum while the lowest PDI was recorded on January 30 when the aforesaid soil factors were minimum. The soil temperature and soil moisture were found positively correlated with disease development. Key words: Stemphylium blight; soil moisture; soil temperature; lentil DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8111 Bangladesh J. Sci. Ind. Res. 46(1), 83-88, 2011